![\left(16^{\sin x}\right)^{\cos x}+\dfrac{6}{4^{\sin^2\left(x-\frac{\pi}{4}\right)}}-4=0
\medskip
\\
2^{2\sin 2x}+6\left(4^{-\sin^2\left(x-\frac{\pi}{4}\right)}\right)-4=0
\medskip
\\
\left(2^{\sin 2x}\right)^2+6\left(4^{-\left(\sin x\cos\frac{\pi}{4}-\cos x\sin\frac{\pi}{4}\right)^2}\right)-4=0
\medskip
\\
\left(2^{\sin 2x}\right)^2+6\left(4^{-\left(\frac{\sqrt{2}}{2}\sin x-\frac{\sqrt{2}}{2}\cos x\right)^2}\right)-4=0 \left(16^{\sin x}\right)^{\cos x}+\dfrac{6}{4^{\sin^2\left(x-\frac{\pi}{4}\right)}}-4=0
\medskip
\\
2^{2\sin 2x}+6\left(4^{-\sin^2\left(x-\frac{\pi}{4}\right)}\right)-4=0
\medskip
\\
\left(2^{\sin 2x}\right)^2+6\left(4^{-\left(\sin x\cos\frac{\pi}{4}-\cos x\sin\frac{\pi}{4}\right)^2}\right)-4=0
\medskip
\\
\left(2^{\sin 2x}\right)^2+6\left(4^{-\left(\frac{\sqrt{2}}{2}\sin x-\frac{\sqrt{2}}{2}\cos x\right)^2}\right)-4=0](https://tex.z-dn.net/?f=%5Cleft%2816%5E%7B%5Csin+x%7D%5Cright%29%5E%7B%5Ccos+x%7D%2B%5Cdfrac%7B6%7D%7B4%5E%7B%5Csin%5E2%5Cleft%28x-%5Cfrac%7B%5Cpi%7D%7B4%7D%5Cright%29%7D%7D-4%3D0%0A%5Cmedskip%0A%5C%5C%0A2%5E%7B2%5Csin+2x%7D%2B6%5Cleft%284%5E%7B-%5Csin%5E2%5Cleft%28x-%5Cfrac%7B%5Cpi%7D%7B4%7D%5Cright%29%7D%5Cright%29-4%3D0%0A%5Cmedskip%0A%5C%5C%0A%5Cleft%282%5E%7B%5Csin+2x%7D%5Cright%29%5E2%2B6%5Cleft%284%5E%7B-%5Cleft%28%5Csin+x%5Ccos%5Cfrac%7B%5Cpi%7D%7B4%7D-%5Ccos+x%5Csin%5Cfrac%7B%5Cpi%7D%7B4%7D%5Cright%29%5E2%7D%5Cright%29-4%3D0%0A%5Cmedskip%0A%5C%5C%0A%5Cleft%282%5E%7B%5Csin+2x%7D%5Cright%29%5E2%2B6%5Cleft%284%5E%7B-%5Cleft%28%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B2%7D%5Csin+x-%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B2%7D%5Ccos+x%5Cright%29%5E2%7D%5Cright%29-4%3D0)
![\left(2^{\sin 2x}\right)^2+6\left(4^{-\frac{1}{2}\left(\sin x-\cos x\right)^2\right)-4=0
\medskip
\\
\left(2^{\sin 2x}\right)^2+6\left(4^{-\frac{1}{2}\left(1-\sin 2x\right)\right)-4=0
\medskip
\\
\left(2^{\sin 2x}\right)^2+6\left(2^{\sin 2x-1}\right)-4=0
\medskip
\\
\left(2^{\sin 2x}\right)^2+3\left(2^{\sin 2x}\right)-4=0
\medskip
\\
2^{\sin 2x}=t \Rightarrow t^2+3t-4=0
\medskip
\\
(t+4)(t-1)=0 \left(2^{\sin 2x}\right)^2+6\left(4^{-\frac{1}{2}\left(\sin x-\cos x\right)^2\right)-4=0
\medskip
\\
\left(2^{\sin 2x}\right)^2+6\left(4^{-\frac{1}{2}\left(1-\sin 2x\right)\right)-4=0
\medskip
\\
\left(2^{\sin 2x}\right)^2+6\left(2^{\sin 2x-1}\right)-4=0
\medskip
\\
\left(2^{\sin 2x}\right)^2+3\left(2^{\sin 2x}\right)-4=0
\medskip
\\
2^{\sin 2x}=t \Rightarrow t^2+3t-4=0
\medskip
\\
(t+4)(t-1)=0](https://tex.z-dn.net/?f=%5Cleft%282%5E%7B%5Csin+2x%7D%5Cright%29%5E2%2B6%5Cleft%284%5E%7B-%5Cfrac%7B1%7D%7B2%7D%5Cleft%28%5Csin+x-%5Ccos+x%5Cright%29%5E2%5Cright%29-4%3D0%0A%5Cmedskip%0A%5C%5C%0A%5Cleft%282%5E%7B%5Csin+2x%7D%5Cright%29%5E2%2B6%5Cleft%284%5E%7B-%5Cfrac%7B1%7D%7B2%7D%5Cleft%281-%5Csin+2x%5Cright%29%5Cright%29-4%3D0%0A%5Cmedskip%0A%5C%5C%0A%5Cleft%282%5E%7B%5Csin+2x%7D%5Cright%29%5E2%2B6%5Cleft%282%5E%7B%5Csin+2x-1%7D%5Cright%29-4%3D0%0A%5Cmedskip%0A%5C%5C%0A%5Cleft%282%5E%7B%5Csin+2x%7D%5Cright%29%5E2%2B3%5Cleft%282%5E%7B%5Csin+2x%7D%5Cright%29-4%3D0%0A%5Cmedskip%0A%5C%5C%0A2%5E%7B%5Csin+2x%7D%3Dt+%5CRightarrow+t%5E2%2B3t-4%3D0%0A%5Cmedskip%0A%5C%5C%0A%28t%2B4%29%28t-1%29%3D0)
0 \Rightarrow \varnothing
\medskip
\\
2)~t=1
\medskip
\\
2^{\sin 2x}=2^0
\medskip
\\
\sin 2x=0
\medskip
\\
2x=\pi l,~l\in\mathbb{Z}
\medskip
\\
x=\dfrac{\pi l}{2},~l\in\mathbb{Z}" alt="1)~t=-4
\medskip
\\
2^{\sin 2x}=-4
\medskip
\\
\left(\forall x\in\mathbb{R}\right)2^{\sin 2x}>0 \Rightarrow \varnothing
\medskip
\\
2)~t=1
\medskip
\\
2^{\sin 2x}=2^0
\medskip
\\
\sin 2x=0
\medskip
\\
2x=\pi l,~l\in\mathbb{Z}
\medskip
\\
x=\dfrac{\pi l}{2},~l\in\mathbb{Z}" align="absmiddle" class="latex-formula">
Ответ. ![x=\dfrac{\pi l}{2},~l\in\mathbb{Z} x=\dfrac{\pi l}{2},~l\in\mathbb{Z}](https://tex.z-dn.net/?f=x%3D%5Cdfrac%7B%5Cpi+l%7D%7B2%7D%2C%7El%5Cin%5Cmathbb%7BZ%7D)